MANAGEMENT OF TECHNOLOGICAL PROCESSES OF OPERATION OF WATER SYSTEMS - Anatoly Valentinovich Maikov (Современная наука и инновации)
The article considers general approaches to the management of operating modes of water-bearing horizons in optimal regimes. The task is to justify the objective function of the object and to construct a regulator.